Edukasi Pengendalian Hazard dan Risiko Kerja pada Kelompok Nelayan di Desa Kampung Beru, Kecamatan Galesong, Kabupaten Takalar: Edukasi Pengendalian Hazard dan Risiko Kerja pada Kelompok Nelayan di Desa Kampung Beru, Kecamatan Galesong, Kabupaten Takalar - Syafitri, Nurul Mawaddah; Hamid, Fatmawati; M. Anas (Education and Talent Development Center Indonesia, 2025)
Fishermen's work has significant health risks due to unhealthy and unsafe behavior, occupational hazards, and work environments. The purpose of this community service activity is to provide education or knowledge to the fishing community regarding the control of hazards or dangers and work risks. This community service activity was carried out at the Kampung Beru Village Office, Galesong District, Takalar Regency on January 18, 2025 with 46 participants. The approach method in implementing this community service activity includes lectures. The activity lasts for 2 hours. The material related to education on controlling occupational hazards and risks for fishermen is explained starting from data on accident cases by fishermen while working, the concept of OSH, potential hazards and risks to fishermen while working (physical, chemical, biological, ergonomic and psychosocial hazards), controlling hazards and risks for fishermen consisting of preparation before sailing, while sailing/at sea and after sailing. Based on the results of this community service activity, it can be concluded that descriptively, the output of this activity is an increase in public knowledge regarding the control of occupational hazards and risks that can be faced by fishermen while working. The community response to the implementation of this activity was very enthusiastic. Seeing the activeness of several counseling participants who asked questions during the presentation of the material. The suggestion for this activity is that data collection should be carried out on similar activities such as pretests and posttests to determine the success of the activity and to determine whether there is an increase in participant knowledge objectively.